The development of electronic student worksheets (e-LKPD) economic materials accounting cycle based on problem-based learning (PBL) companies - Jhohan Untung; Endah Andayani; Auliana Farabbanie Al Arsy (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
This development research aims to produce electronic student worksheets (E-LKPD) in the economics subject of trading company accounting which is a logical science and requires high reasoning to understand it so that the problem-based learning model is very appropriate by adding real-world problems that students must solve before start learning, so it is necessary to analyze the E-LKPD development process and its feasibility. LKPD has been conventionally inefficient and unable to facilitate online learning. The researcher used research and development (R&D) research, using the modified 4D development modified model of Thiagarajan without performing the disseminate stage. The result of the feasibility validation of the four validators are as follows; (1) Validation of material gained 92.5% with a very decent category with rich advantages in sales and purchase transactions; (2) Validation of learning design experts scored 93.75% with a very decent category with the excellent of case studies; (3) Validation of linguists gained 95% with a very decent dictionary with easy-to-understand linguistic clarity and (4) Validation of learning technologist gained 92.7% with the advantage of very simple and easy-to-use technology. The implications of this study can be an alternative to completing distance learning while preparing the important instruments in the face of a free curriculum.